Analysis of the Needs of Cognitive Conflict-Based Teaching Materials Integrated with Augmented Reality on Heat - muttasyabiha, muttasyabiha (Department of Physics Universitas Negeri Padang, 2024)
In the 21st century, the increasing development of technology and informatics has brought significant changes in the world of education. The independent curriculum is a response to the demands of education in the era of evolving technology. The main goal is to deepen concept understanding and strengthen student skills. Concept understanding is one of the basic competencies in the independent curriculum that students must have. But in fact, based on research of preliminary, it was got that the problem of concepts understanding from students was still low and tended to occur misconceptions, the use of cognitive conflict learning could contribute to improving understanding of concepts in the independent curriculum. The research purposes was to analyze the characteristics, validity, and practicality of teaching materials based on cognitive conflict. This research type is preliminary research. Three Padang City High School teachers were given a questionnaire to complete in order to assess how physics is being taught in classrooms. Subsequently, the survey was distributed to 130 students in class XI F across two distinct high schools in Padang City, with the objective of examining the requirements for physics educational resources in the classroom. Journal analysis was done in addition to the questionnaire to examine high school students' conceptual grasp of heat topic. Both quantitative and qualitative analyses were done on the data. Misconceptions about hot content and low concept understanding among students are the outcome of an analysis of multiple published papers. Furthermore, there are still few teaching resources available, less technology-integrated learning media, and a teacher-centered approach to education. Consequently, based on the findings of preliminary research, physics instructional materials integrating augmented reality technology and cognitive conflict must be developed